Screening strategies for adults with type 2 diabetes mellitus - Mearns, Helen (Department of Public Health and Family Medicine, 2022)
There are insufficient randomized controlled trials to address whether screening for type 2 diabetes mellitus (T2DM) improves health outcomes. This systematic review sought to cast a wider net and synthesise evidence from non-randomised intervention studies to assess the effectiveness of T2DM screening in adults for reducing mortality and T2DM-associated morbidity. We searched PubMed/MEDLINE, Scopus, Web of Science, CINAHL, Academic Search Premier and Health Source Nursing Academic (inception onwards; last search July 2021). We included non-randomised intervention studies that assessed T2DM screening compared to no screening, in adults without known T2DM. Screening was performed independently by two reviewers. Data was abstracted by one reviewer and checked by a second, as was risk of bias (ROBINS-I) and certainty of evidence (GRADE). A narrative summary was performed. We screened 10,892 records, retrieving 67 for full-text screening with one record meeting inclusion criteria. The study was a prospective cohort comparing T2DM screening versus no screening. It included adults, 40 - 65 years, with no known T2DM from a single community practice in Ely, England (N = 4,936) and evaluated outcomes at two time periods. The study was assessed as having moderate risk of bias. There may be little or no difference in mortality between those who were invited to screening versus those who were not invited (1990-1999: adjusted hazard ratio (aHR) 0.79 [95% confidence interval (CI) 0.63 – 1.00], n = 4,936, low certainty evidence and 2000 - 2008: aHR 1.18 [95% CI 0.93 - 1.51], n = 3,002, low certainty evidence). We found only one study reporting the effectiveness of screening for T2DM in adults. Therefore, despite ongoing T2DM screening in clinical care, this review highlights an important research gap in understanding the true health benefits of screening.